(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
This article describes the establishment of the Hazarasp Free Economic Zone (hereinafter referred to as FEZ) in Khorezm region, its specific economic and geographical features, including economic and geographical location, natural resources and transport infrastructure, as well as utilities and labor resources. location, as well as short-term achievements and future development. Numerous guidelines and scientific literature, as well as relevant laws, decrees and resolutions of the President of the Republic of Uzbekistan, resolutions of the Cabinet of Ministers, as well as websites were used in the development of scientific recommendations and proposals for the Hazarasp FEZ.